The burden of unintended pregnancies in Brazil: a social and public health system cost analysis - Le HH; Connolly MP; Bahamondes L; Cecatti JG; Yu J; Hu HX (Dove Medical Press, 2014)
Hoa H Le,1 Mark P Connolly,1,2 Luis Bahamondes,3 Jose G Cecatti,3 Jingbo Yu,4 Henry X Hu4 1Department of Pharmacoeconomics and Pharmacoepidemiology, University of Groningen, Groningen, the Netherlands; 2Global Market Access Solutions, Saint-Prex, Switzerland; 3Department of Obstetrics and Gynecology, School of Medical Sciences, University of Campinas, Campinas, Brazil; 4Merck & Co, Whitehouse Station, NJ, USA Background: Unintended pregnancy (UP) is an unmet medical need with consequences worldwide. We evaluate the costs of UP based on pregnancies in Brazil from for the year 2010. Methods: The consequences of UP were evaluated using decision analysis based on pregnancy rates and outcomes as miscarriage, induced abortion, and live birth, which were factored into the analysis. The model discriminated between maternal and child outcomes and accounted for costs (in Brazilian currency [Real$, R$]) within the Brazilian public health service attributed to preterm birth, neonatal admission, cerebral palsy, and neonatal and maternal mortality. Event probabilities were obtained from local resources. Results: We estimate that 1.8 million UPs resulted in 159,151 miscarriages, 48,769 induced abortions, 1.58 million live births, and 312 maternal deaths, including ten (3%) attributed to unsafe abortions. The total estimated costs attributed to UP are R$4.1 billion annually, including R$32 million (0.8%) and R$4.07 billion (99.2%) attributed to miscarriages and births and complications, respectively. Direct birth costs accounted for approximately R$1.22 billion (30.0%), with labor and delivery responsible for most costs (R$988 million; 24.3%) for the year 2010. The remainder of costs were for infant complications (R$2.84 billion; 72.3%) with hospital readmission during the first year accounting for approximately R$2.15 billion (52.9%). Based on the national cost, we estimate the cost per UP to be R$2,293. Conclusion: Despite weaknesses in precise estimates in annual pregnancies and induced abortions, our estimates reflect the costs of UP for different pregnancy outcomes. The main costs associated with UP are in those carried to parturition. The health cost of abortion represents a small proportion of total costs as these are paid for outside of the public health system. Consequently, reductions in UP will generate not only cost savings, but reductions in woman and child morbidity and mortality. Keywords: unintended pregnancy, public health, Brazil, abortion